2020
DOI: 10.1097/sle.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Inguinal Hernia Repair: Robotic TAPP Versus Laparoscopic TEP

Abstract: The authors state that this study has been approved by the appropriate institutional and research ethics committee and has been performed in accordance with the ethical standards as laid down in the 1964 Declaration of Helsinki and its later amendments or comparable ethical standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, only a few studies comparing the laparoscopic and the robotic approach have been published [ 4 16 ]. The majority of them were characterized by small sample size, especially in the robotic arm, [ 6 , 7 , 9 , 16 , 17 ], limiting the power and, thus, the generalizability, of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies comparing the laparoscopic and the robotic approach have been published [ 4 16 ]. The majority of them were characterized by small sample size, especially in the robotic arm, [ 6 , 7 , 9 , 16 , 17 ], limiting the power and, thus, the generalizability, of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…As the US population ages, it will be increasingly important to identify best practices when it comes to surgical care for older adults. Studies have shown that robotic ventral hernia repairs can provide clinical benefits, such as lower rates of wound complications 15,16 and shorter length of stays 10,16 compared to open approaches. However, there is no data examining the role of robotic surgery in retromuscular hernia repair specifically in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, comparison of rTAPP and TEP shows controversial results. Some studies report lower pain scores and a lower incidence of complications for rTAPP compared to TEP [ 12 13 ]. Others show comparable results regarding postoperative outcomes such as pain, surgical site infection, hospital length of stay and recurrence rate [ 14 15 ].…”
Section: Introductionmentioning
confidence: 99%